MAKNA ANAK LAKI-LAKI DI MASYARAKAT BATAK TOBA (Studi kasus di Kota Sidikalang Kabupaten Dairi Provinsi Sumatera Utara) - Judika N Sianturi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The studies aims to determine and analyze the meaning of the boy in town Sidikalang Dairi. This study is qualitative study that analyzed descriptively. The theory used in this research is the theory of structural functional by the Parson. In this study the number of respondents as many as seven people. A sampling technique is Purposive samplin. The results of the field say that the child is gift from God that is in forward,especially those in the public Batak Toba highly preferred boys because the boys are bearres of the clan and descendant successor to the family Batak Toba. Child is the pride of the community Batak Toba .Batak Toba children in the community as well as additions (sahala) authority for the parents so that the Toba Batak people do not have the boy felt like there was less because if it does not have the boy's family line will be extinct Keywords: Custom,Meaning Boy,Batak Toba.